MEN1 Tumor Suppressor Gene is Required for Long-term Memory Formation in an Aversive Operant Conditioning Model of Lymnaea stagnalis. (21st May 2018) - Dong, Nancy; Senzel, Anthony; Li, Kathy; Lu, Tom Z.; Guo, Cong-Hui; Aleksic, Mila; Feng, Zhong-Ping
Highlights: We investigated the role of the tumor suppressor gene Men1 in aversive long-term memory formation in Lymnaea stagnalis. Aversive long-term memory was associated with up-regulated Men1 gene expression. In vivo Men1 knockdown prevented aversive long-term memory formation and conditioning-induced changes in neuronal firing. Men1 knockdown did not affect conditioning-induced up-regulation of creb gene expression. Abstract: Activity-dependent transcription factors critically coordinate the gene expression program underlying memory formation. The tumor suppressor gene, MEN1, encodes a ubiquitously expressed transcription regulator required for synaptogenesis and synaptic plasticity in invertebrate and vertebrate central neurons . In this study, we investigated the role of MEN1 in long-term memory (LTM) formation in an aversive operant conditioning paradigm in the freshwater pond snail Lymnaea stagnalis ( L. stagnalis ). We demonstrated that LTM formation is associated with an increased expression of MEN1 coinciding with an up-regulation of creb1 gene expression. In vivo knockdown of MEN1 prevented LTM formation and conditioning-induced changes in neuronal activity in the identified pacemaker neuron RPeD1. Our findings suggest the involvement of a new pathway in LTM consolidation that requires MEN1- mediated gene regulation.